Design of internet of things service system for logistics engineering by using the blockchain technology. (15th May 2023) - Shen, Aiming
With the rapid progress of information technology, the application of the Internet of things (IoT) technology has become more common, which also brings greater challenges to the IoT service system. Most small and medium-sized foreign trade enterprises rely on the third-party cross-border e-commerce platform to carry out retail export business. The logistics service system has the problems of long time-consuming and high transportation and management costs. The centralised management system makes the cooperation and information sharing between IoT devices under different platforms difficult, and the device privacy data are easily leaked. In order to solve the above problems and improve the level of logistics warehousing management, an intelligent warehousing management system (WMS) has become a hot topic. Blockchain technology is introduced to build an intelligent WMS model based on the existing technical level of warehouse management.